Desenvolvimento e caracterização de nanopartículas poliméricas inaláveis para vetorização de macrófagos e tratamento da tuberculose - (:unkn) unknown (Universidade Estadual de Goiás, 2019)
Tuberculosis is an infectious disease caused by Mycobacterium tuberculosis, whose oral treatment presents drawbacks such as systemic side effects and prolonged treatment, decreasing patient compliance. The development of polymeric nanoparticles for pulmonary administration can improve the treatment of tuberculosis, making it possible to transport the drug to the site of action and to target the alveolar macrophages. Poly(ethylene carbonate) is a biodegradable polymer with surface degradation which can be used for the controlled release of drugs. This polymer has specific degradation by the enzyme cholesterol esterase and by macrophages, being therefore interesting for the application in the treatment of tuberculosis. The aims of this work were to conduct a compatibility study between clofazimine, a drug used in the treatment of multidrug-resistant tuberculosis, and excipients commonly used for the preparation of polymeric nanosystems; and the development and physico-chemical characterization of inhaled nanoparticles of poly(ethylene carbonate) containing clofazimine. Through the analysis of differential scanning calorimetry, thermogravimetry and infrared spectroscopy, the amorphization of the drug in the presence of the polymers, poly-ɛ-caprolactone (PCL), poly(D,L-lactide) (PLA), poly(D,L-lactide-coglycolide)-alkyl esther (75:25) (PLGA75:25) and poly(D,L-lactide-co-glycolide)-esther (85:15) (PLGA85:15), indicating that the drug interacts with these polymers and alters its crystalline characteristic. The solubilization of the drug in the adjuvants Span 60®, Span 80®, Span 85®, Poloxamer 188, Poloxamer 407, polyvinyl alcohol (PVA), Tween 80® and oleic acidwas also observed. This characteristic is important for the development of the nanoparticles, since it increases drug encapsulationNanocapsules and nanospheres were prepared by nanoprecipitation technique. The particles were characterized for their mean diameter and polydispersion index (PdI) by dynamic light scattering, encapsulation efficiency (EE) by high performance liquid chromatography, freeze-drying, thermal analysis by calorimetry,stability of nanoparticles in simulated biological fluids and nanoparticle tracking analysis (NTA). . The two nanocapsules formulations showed average sizes of 210 and 237 nm, PdI 0.16 and EE of 65%. Nanospheres showed average size of 196 and 438 nm, PdI 0.43-0.30 and EE 46.85 and 53.95%. The formulations were freeze-dried using sucrose, trehalose and mannitol as cryoprotectants at 1.5%, 2.5%, 5%, 10% and 15% (w/v). Among the cryoprotectants evaluated, 10% mannitol allowed for the best particle redispersibility after freeze-drying. Particles remained stable without aggregation when incubated with PBS, 0.08% (w/v) mucin and 0.1% mucin (w/v). The nanoparticle tracking analysis showed that nanoparticles were able to move through the mucin. The results obtained in this work demonstrate the viability of producing polymeric nanoparticles for local release of clofazimine in the lungs, e will sypport further studies of the developed nanoparticulate system, and the in vitro evaluation of its activity Key words:
Keywords: Poli(etileno carbonato); Clofazimina; Mycobacterium tuberculosis; Poly(ethylene carbonate); Nanotechnology; Clofazimine; Mycobacterium tuberculosis; CIENCIAS DA SAUDE